Introducing dynamic consent for improved trust and privacy in research involving human biological material and associated data in South Africa - Prinsen, Larisse (Frontiers in Genetics, 2024)
Biomedical research using human biological material and data is essential for improving human health, but it requires the active participation of many human volunteers in addition to the distribution of data. As a result, it has raised numerous vexing questions related to trust, privacy and consent. Trust is essential in biomedical research as it relates directly to the willingness of participants to continue participating in research. Privacy and the protection of personal information also influence trust. Informed consent has proven to be insufficient as it cannot overcome the informational deficit between primary and unknown future uses of material and data and is therefore not fully informed and invalid. Broad consent is also problematic as it takes full control of samples and data flow from the research participant and inherently requires that a participant must trust that the researcher will use their material or data in a manner that they would find acceptable. This paper attempts to offer some insight into how these related issues can be overcome. It introduces dynamic consent as a consent model in research involving human biological material and its associated data. Dynamic consent is explained, as well as its claims of superiority in instances where future research is possible. It is also shown how dynamic consent contributes to better control of the samples and data by the research participant, and how trust may be improved by using this consent model. Dynamic consent’s co-existence with and support of the South African Protection of Personal Information Act of 2013 is also assessed. The limitations of dynamic consent are also discussed.